Epic style: from classical (strict) to free (mixed) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
This article discusses the principles of early classic (strict) epic style, its formation and development, as well as the origin of the later epic style called free or mixed by A. F. Losev. It is defined the essence of epic style at the present stage, with the emergence of the genre of the novel. It is celebrated living weaving of strict and free epic styles, gravitating to the full display of life, to the objectivity, detachment and calm narration.
Keywords: epic; epic poetry; novel; genre; epic style; mania poetry; mimetic art